1996
DOI: 10.1016/0735-1097(96)00204-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced vasodilation in forearm circulation of normal subjects and patients with congestive heart failure: Role of endothelium-derived nitric oxide

Abstract: Regional inhibition of nitric oxide synthase with administration of L-NMMA in the brachial artery significantly decreased forearm blood flows during rhythmic hand grip exercise in normal subjects but not in patients with congestive heart failure. These findings suggest that nitric oxide-mediated vasodilation during submaximal exercise is impaired in the forearm circulation of patients with congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 34 publications
3
78
0
1
Order By: Relevance
“…22 An impairment in NO-dependent vascular function is a common finding in many cardiovascular diseases, including hypertension and heart failure. 11,32 The present findings corroborate the view that ET A receptor blockade is a useful tool in preventing the endogenous ET-dependent component of systemic and renal vasoconstriction secondary to NO deficiency.…”
Section: Montanari Et Al Effects Of L-name and Bq-123 In Human Kidneysupporting
confidence: 79%
“…22 An impairment in NO-dependent vascular function is a common finding in many cardiovascular diseases, including hypertension and heart failure. 11,32 The present findings corroborate the view that ET A receptor blockade is a useful tool in preventing the endogenous ET-dependent component of systemic and renal vasoconstriction secondary to NO deficiency.…”
Section: Montanari Et Al Effects Of L-name and Bq-123 In Human Kidneysupporting
confidence: 79%
“…6,7,20,21,23 Katz et al observed that nitric oxide synthase inhibition reduced exercise-induced blood flow in normal subjects, but not in patients with heart failure, suggesting that nitric oxide-mediated vasodilation during exercise is impaired in individuals with heart failure. 23 In addition, Hirai et al have reported that inhibition of nitric oxide synthase resulted in reduced blood flow to exercising skeletal muscle in rats. 24 In a small human study, Gilligan et al observed that inhibition of nitric oxide synthase resulted in decreased forearm blood flow during hand-grip exercise.…”
Section: Discussionmentioning
confidence: 99%
“…NOS inhibition significantly reduced the forearm vasodilatation response to handgrip exercise in normal individuals, but did not change the response in patients with CHF suggesting that flow-induced NO-mediated vasodilatation during exercise is blunted in these patients [53]. In most CHF patients endothelial-mediated flow-dependent vasodilatation may be reduced as a consequence of physical deconditioning and the mechanistic evidence may be unmasked by studying the effects of exercise training on the endothelial function and exercise performance.…”
Section: The Endotheliummentioning
confidence: 98%